If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -2)(x + 4) = y Reorder the terms: (-2 + X)(x + 4) = y Reorder the terms: (-2 + X)(4 + x) = y Multiply (-2 + X) * (4 + x) (-2(4 + x) + X(4 + x)) = y ((4 * -2 + x * -2) + X(4 + x)) = y ((-8 + -2x) + X(4 + x)) = y (-8 + -2x + (4 * X + x * X)) = y (-8 + -2x + (4X + xX)) = y Reorder the terms: (-8 + 4X + -2x + xX) = y (-8 + 4X + -2x + xX) = y Solving -8 + 4X + -2x + xX = y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 4X + -2x + 8 + xX = 8 + y Reorder the terms: -8 + 8 + 4X + -2x + xX = 8 + y Combine like terms: -8 + 8 = 0 0 + 4X + -2x + xX = 8 + y 4X + -2x + xX = 8 + y Add '2x' to each side of the equation. 4X + -2x + 2x + xX = 8 + 2x + y Combine like terms: -2x + 2x = 0 4X + 0 + xX = 8 + 2x + y 4X + xX = 8 + 2x + y Reorder the terms: -8 + 4X + -2x + xX + -1y = 8 + 2x + y + -8 + -2x + -1y Reorder the terms: -8 + 4X + -2x + xX + -1y = 8 + -8 + 2x + -2x + y + -1y Combine like terms: 8 + -8 = 0 -8 + 4X + -2x + xX + -1y = 0 + 2x + -2x + y + -1y -8 + 4X + -2x + xX + -1y = 2x + -2x + y + -1y Combine like terms: 2x + -2x = 0 -8 + 4X + -2x + xX + -1y = 0 + y + -1y -8 + 4X + -2x + xX + -1y = y + -1y Combine like terms: y + -1y = 0 -8 + 4X + -2x + xX + -1y = 0 The solution to this equation could not be determined.
| 3d=3d+9 | | 12w-4= | | -32-5m=7m+8 | | 15x^2+11=86 | | 2-5Xw= | | 0.4(x-2)=9.2 | | 3x(2x+1)=2x+11 | | L=28+8k | | 2(6w-2)= | | 3w-2.4=1.8 | | 3x^3+3x^2+2x=0 | | w+w+5w+5w-2= | | 2m-4s=9 | | 75-9g=2(3-f) | | -3-x-x^2=0 | | 5(x+7)+2=-4(x-3)-11 | | Log[4x+9]=5 | | 7(x-7)-5=25x-108 | | 75-9g= | | 13/15//7/10 | | 4v+20-4=34 | | Log(4x+9)=5 | | x+x*19.6=4280 | | -16t^2+10t+26=0 | | 12x^2+16=172 | | x/9=251 | | 6(x+4)-5[x-(2x-3)]= | | -2(x-3)+5=3(x+4)+8 | | 3=3+y*.08 | | X+19=45 | | 16x^4-x-1=0 | | 16-3*(8-3)*2/5 |